2006
DOI: 10.1167/iovs.05-1530
|View full text |Cite
|
Sign up to set email alerts
|

NoVSX1Gene Mutations Associated with Keratoconus

Abstract: Only one of the presumed pathogenic mutations in the VSX1 gene, Asp144Glu, was identified in a single member of the cohort of affected patients. However, as previously demonstrated, Asp144Glu is a non-disease-causing polymorphism. The absence of pathogenic mutations in the VSX1 gene in a large number of unrelated KTCN patients indicates that other genetic factors are involved in the development of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 26 publications
2
50
0
3
Order By: Relevance
“…This mutation is transmitted as an autosomal dominant trait with variable expressivity and incomplete penetrance. Although Aldave et al (2006) identified only one mutation, D144E, in a single affected keratoconus patient, D144E is a non-disease-causing polymorphism. Liskova et al (2007) reported the D144E mutation and two novel intronic SNPs in a white British family, but these variants did not cosegregate with the disease phenotype.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This mutation is transmitted as an autosomal dominant trait with variable expressivity and incomplete penetrance. Although Aldave et al (2006) identified only one mutation, D144E, in a single affected keratoconus patient, D144E is a non-disease-causing polymorphism. Liskova et al (2007) reported the D144E mutation and two novel intronic SNPs in a white British family, but these variants did not cosegregate with the disease phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…Tang et al (2008) could not confirm the association of the three polymorphisms L159 M, R166 W, and H244R in the VSX1 gene in a larger pedigree with keratoconus because the distribution of the three polymorphisms was not significant enough to support a pathogenetic role in keratoconus. Aldave et al (2006) and Tang et al (2008) reported that the previously identified pathogenic mutations did not observe the association with sporadic keratoconus patients. Therefore, it is important to identify the genetic factors that determine susceptibility to keratoconus to gain insight into the pathogenesis of keratoconus in Korean patients because the susceptibility of mutations in VSX1 can vary in different ethnicities.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…61 To date, more than 1500 KC patients have been screened for VSX1 and potentially pathogenic mutations have been identified in less than 2% of cases suggesting that this gene does not have a major role in the molecular pathology of KC. 60,[62][63][64] Other candidate genes screened in KC cohorts include TIMP3, 65 TGFBI, 66,67 ZEB1, 68 FLG 69 and several collagen genes. 46,70,71 Despite these efforts, potentially pathogenic variants have only been identified in a very small number of individuals with KC.…”
Section: Geneticsmentioning
confidence: 99%
“…Rabinowitz et al identified a gene locus on chromosome 21q, which encodes a collagen and defines the relationship between the DS and the keratoconus (23). However, gene loci on chromosomes 20, 16, and 15 related to keratoconus were also identified (24)(25)(26). Keratoconus seems multifactorial and includes genetic and environmental aspects.…”
Section: Discussionmentioning
confidence: 99%